Immune mechanisms of Concanavalin A model of autoimmune hepatitis - Wang, Hai-Xia (World journal of gastroenterology : WJG, 2012)
As a chronic inflammatory disease of the liver,the pathogenic mechanisms of autoimmune hepatitis （AIH） have not yet been elucidated,with prognosis and diagnosis remaining unsatisfied.Currently the only viable treatments of AIH are immunosuppressant application and liver transplantation.It is considered that lack of good animal AIH models is the main reason for the shortage of a simple and efficient cure.The Concanavalin A （Con A） model is a typical and well established model for investigating T-cell and macrophage dependent liver injury in mice,which closely mimics the pathogenesis mechanisms and pathological changes of patients,and is regarded as the best experimental model for AIH research so far.In this paper we eluci-dated the pathogenic mechanisms of AIH and the evolution of relative animal models.We go on to further focus on Con A-induced liver injury from the point of immunological mechanisms and the change of cytokine levels.Finally,we manifested the clinical significance of the AIH animal models and the challenges they would meet during their future development.